1993
DOI: 10.1159/000187140
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Peritoneal Transport during Continuous Ambulatory Peritoneal Dialysis and Its Impact on Ultraf iltration, Loss of Macromolecules and Plasma Level of Proteins, Lipids and Lipoproteins

Abstract: We investigated the effect of heterogeneity in the peritoneal transport of plasma proteins on dialysis efficiency and plasma levels of proteins, lipids and lipoproteins in 32 patients undergoing long-term continuous ambulatory peritoneal dialysis (CAPD; 9 females and 23 males, 18-76 years old). Eleven patients were studied on several occasions (at 0-42 months) and the remainder at 6-60 months on CAPD (n = 49). We have divided our patients arbitrarily into two equal groups according to their protein concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…and IgM levels in sera and in concentrated dialysates were measured by nephelometry [16]. The peritoneal mass transfer (D • V/T; mass/h) and clearance (D/P-V/T; ml/min) of all solutes were calculated as described previously [10,11], where Pand D are serum and dialysate concentrations of solute, and V and T are intraperitoneal dialysate volumes and dwell time intervals, respectively. Because the V/T val ues in these two equations were identical for different solutes in the same patients, we decided to delete V/T and compare peritoneal sol ute transport by D or D/P ratios.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and IgM levels in sera and in concentrated dialysates were measured by nephelometry [16]. The peritoneal mass transfer (D • V/T; mass/h) and clearance (D/P-V/T; ml/min) of all solutes were calculated as described previously [10,11], where Pand D are serum and dialysate concentrations of solute, and V and T are intraperitoneal dialysate volumes and dwell time intervals, respectively. Because the V/T val ues in these two equations were identical for different solutes in the same patients, we decided to delete V/T and compare peritoneal sol ute transport by D or D/P ratios.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of peritoneal albumin loss and heterogeneous peritoneal solute transport on SA lev els have not been fully elucidated [11][12][13][14] and are further investigated in the present study.…”
Section: Group 1 Group 2 Group 3 (N = 5)mentioning
confidence: 98%
“…It is well known that CAPD patients lose substantial amount of proteins into the peritoneal dialysate, resembling the protein losses observed in NS. This protein loss may, in turn, stimulate the hepatic production of albumin and cholesterol-enriched lipoproteins thus leading to elevated concentrations of LDL-cholesterol and Lp(a) [97,98,99,100,101]. In addition, the absorption of glucose from the dialysis fluid and the resultant increase in insulin levels may enhance the hepatic synthesis and secretion of VLDL and possibly that of other lipoproteins such as Lp(a) [102].…”
Section: Lipids In Hemodialysis and Peritoneal Dialysismentioning
confidence: 99%
“…As discussed above, does a decreasing albumin concentration represent a greater risk for death than a patient with a low but stable serum albumin? Some authors have suggested that independent of dialysis dose serum albumin concentrations are inversely correlated with peritoneal membrane trans port types [46,[62][63][64], These data suggest that patients who tend to be rapid transporters have lower serum albumin levels than low transporters. Nolph et al [63] also found a lower LBM in high transporters, but no differ ence in body weight or surface area.…”
Section: Does the Serum Albumin Concentration Represent The Same Relamentioning
confidence: 99%
“…6). As discussed above, these patients tend to have lower albumin levels [61,62,64] despite equal doses of dialysis [63]. Perhaps, in these patients this increased glucose load during classic CAPD due to the long dwells and the need to use hypertonic fluids results in an overall decrease in appetite or a lesser propor tion of their caloric intake as protein.…”
Section: Is It Beneficial To Match Dwell Time To Peritoneal Membrane mentioning
confidence: 99%